2012
DOI: 10.1667/rr2773.1
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-Induced Vascular Damage in Tumors: Implications of Vascular Damage in Ablative Hypofractionated Radiotherapy (SBRT and SRS)

Abstract: We have reviewed the studies on radiation-induced vascular changes in human and experimental tumors reported in the last several decades. Although the reported results are inconsistent, they can be generalized as follows. In the human tumors treated with conventional fractionated radiotherapy, the morphological and functional status of the vasculature is preserved, if not improved, during the early part of a treatment course and then decreases toward the end of treatment. Irradiation of human tumor xenografts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
399
4
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 469 publications
(422 citation statements)
references
References 90 publications
15
399
4
4
Order By: Relevance
“…Similar results were reported in another study on metastatic RCC (24), in which a univariate analysis revealed dose per fraction ≥9 Gy (HR =0.631; 95% CI, 0.429-0.931; P=0.021) to be predictive factor for (25). These data support the concept that a dose per fraction >10 Gy may independently of the histological type of the cancer induce severe vascular damage leading to indirect cell death (26).…”
Section: Discussionsupporting
confidence: 88%
“…Similar results were reported in another study on metastatic RCC (24), in which a univariate analysis revealed dose per fraction ≥9 Gy (HR =0.631; 95% CI, 0.429-0.931; P=0.021) to be predictive factor for (25). These data support the concept that a dose per fraction >10 Gy may independently of the histological type of the cancer induce severe vascular damage leading to indirect cell death (26).…”
Section: Discussionsupporting
confidence: 88%
“…As oxygen is an important factor in determining tumor response to RT, those data suggest that carbon-ion therapy may be superior to other forms of irradiation. Hypofractionated RT at higher doses per fraction may enhance radiation-induced tumor cell death by inducing endothelial apoptosis and subsequent microvascular damage (20,21). Alternatively, modern RT modalities, including CyberKnife, IMRT and stereotactic RT (SRT), deliver photons and provide larger irradiated doses with OAR sparing when compared with conventional techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Doses >10 Gy likely produce secondary cell elimination due to enhanced vascular damage (20,21). Compared with conventional schedules, we used relatively large doses per fraction, which potentially caused differences in biological reactions following radiation exposure.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to inducing double-strand DNA breaks similar to conventionally fractionated treatment regimes, 21 RT delivered at higher doses per fraction (8-10 Gy) may induce more significant vascular, stromal and antitumour immune responses within the local tumour microenvironment, 22,23 leading to increased cell death and improved efficacy.…”
Section: Stereotactic Radiation-a Novel Opportunity To Improve Radiotmentioning
confidence: 99%